2013
DOI: 10.1002/jsfa.6450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total phenolics, flavonoids and antioxidant activity of 18 Korean onion cultivars: a comparative study

Abstract: Among the 18 cultivars, Sunpower is the most promising in terms of total phenolics, total flavonoids and antioxidant activity. Our results suggest that day length sensitivity/ripening among the cultivars do not play any significant role for high values of total phenolics, flavonoids and antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…For antioxidant compounds extraction, ethanol aqueous solution is a preferred solvent system (Karacabey & Mazza, 2010;Sharma et al, 2014), since polyphenols have a varied range of solubility (Ilaiyaraja, Likhith, Sharath Babu, & Khanum, 2015), and use of solvents with different polarity potentials high yield of total antioxidants (Szydłowska-Czerniak, Tułodziecka, Karlovits, & Szłyk, 2015). Ethanol, a green safe solvent, (Kukula-Koch et al, 2013;Li et al, 2012) was utilized due to efficiency on solubilizing bioactive molecules from vegetable matrixes (Espinosa-Pardo et al, 2014;Fang, Wang, Hao, Li, & Guo, 2015;Sharma et al, 2014).…”
Section: Antioxidant Compounds Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…For antioxidant compounds extraction, ethanol aqueous solution is a preferred solvent system (Karacabey & Mazza, 2010;Sharma et al, 2014), since polyphenols have a varied range of solubility (Ilaiyaraja, Likhith, Sharath Babu, & Khanum, 2015), and use of solvents with different polarity potentials high yield of total antioxidants (Szydłowska-Czerniak, Tułodziecka, Karlovits, & Szłyk, 2015). Ethanol, a green safe solvent, (Kukula-Koch et al, 2013;Li et al, 2012) was utilized due to efficiency on solubilizing bioactive molecules from vegetable matrixes (Espinosa-Pardo et al, 2014;Fang, Wang, Hao, Li, & Guo, 2015;Sharma et al, 2014).…”
Section: Antioxidant Compounds Extractionmentioning
confidence: 99%
“…Ethanol, a green safe solvent, (Kukula-Koch et al, 2013;Li et al, 2012) was utilized due to efficiency on solubilizing bioactive molecules from vegetable matrixes (Espinosa-Pardo et al, 2014;Fang, Wang, Hao, Li, & Guo, 2015;Sharma et al, 2014). In addition, previous studies using MAE to the extraction of antioxidant compounds from fruits determined that the concentration of the solvent, microwave power and exposition time were independents variables (Dahmoune et al, 2014Fang et al, 2015;Kim et al, 2012;Li et al, 2012Li et al, , 2014Zeković et al, 2016).…”
Section: Antioxidant Compounds Extractionmentioning
confidence: 99%
“…It should also be noted that different results may also be related to the type of species chosen. In fact, it was shown that components and activities of onion are different on the basis of cultivars [28].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, TPC values of the two methanolic extracts of Spanish onion varieties ranged from 5.15 to 6.33 mg GAE/g DW for white onion, and 2.48 to 2.58 mg GAE/g DW for Calçot de Valls onion. However, it should be noted that TPC values could vary depending on the location of the cultivar and on the solvent used during the extraction process [1,[21][22][23][24].…”
Section: Hplc Analysis Of Flavonols and Anthocyanin And Total Phenolimentioning
confidence: 99%